ISLAMIC EDUCATION PLANNING (Management Of Students In Medan Ikhsan MTs Nurul Year 2019) - Rusli Kembaren; Dewi Sumitra; Rahmat Hidayat (Jurnal Sabilarrasyad, 2020)
This writing uses the kind of writing narrative with keperpustakaan studyand comparative study existing research results. The subject of thisdiscussion is kepalah school. Based on the study results, it can beconcluded that Management Implementation of Students at MTs NurulIkhsan Medanhas been implemented by applying the eight steps inmanagement activities of learners is the analysis of the needs of learners,recruitment of students, selection of students, grouping learners, oriantasi,coaching and development of learners, recording and reporting, as well asgraduation and alumni. but there are some parts of the indicators in theimplementation of management students who are still not optimalimplementation. As in the selection of indicators learners whereMTsNurul Ikhsan do not carry out the selection of students who will goon the MTs but only selection for the class division is attributable to thelack of interest of students to enroll in MTsRaudhatul Ulum.